The 2019 Schizophrenia International Research Society Conference, 10–14 April, Orlando, Florida: A summary of topics and trends. (February 2020) - Alameda, Luis; Ashok, Abhishekh; Avery, Suzanne; Bani-Fatemi, Ali; Berkhout, Susan; Best, Mike; Bonfils, Kelsey; Colizzi, Marco; Dauvermann, Maria; Plessis, Stefan Du; Dwyer, Dominic; Eisner, Emily; et al.
Highlights: A broad range of topics was covered during the first North American SIRS congress. Novel ways of identifying at-risk individuals were addressed. Presenters provided evidence supporting the efficacy of using a multi-dimensional approach to identify schizophrenia symptoms. Abstract: The Schizophrenia International Research Society (SIRS) recently held its first North American congress, which took place in Orlando, Florida from 10-14 April 2019. The overall theme of this year's congress was United in Progress – with the aim of cultivating a collaborative effort towards advancing the field of schizophrenia research. Student travel awardees provided reports of the oral sessions and concurrent symposia that took place during the congress. A collection of these reports is summarized and presented below and highlights the main themes and topics that emerged during the congress. In summary, the congress covered a broad range of topics relevant to the field of psychiatry today.